2021
DOI: 10.3390/ijgi10030140
|View full text |Cite
|
Sign up to set email alerts
|

Post-War Urban Damage Mapping Using InSAR: The Case of Mosul City in Iraq

Abstract: Urban infrastructures have become imperative to human life. Any damage to these infrastructures as a result of detrimental activities would accrue huge economical costs and severe casualties. War in particular is a major anthropogenic calamity with immense collateral effects on the social and economic fabric of human nations. Therefore, damaged buildings assessment plays a prominent role in post-war resettlement and reconstruction of urban infrastructures. The data-analysis process of this assessment is essent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Then, ground control points and the polynomial optimization method were performed for the orbital refinement and the phase re-flattening process [29]. SVD inversion and atmospheric filtering were selected to obtain more accurate LOS displacement, and the results were projected to the vertical direction according to the geometric relationship of incident angle for further analysis [30,31].…”
Section: Data Processingmentioning
confidence: 99%
“…Then, ground control points and the polynomial optimization method were performed for the orbital refinement and the phase re-flattening process [29]. SVD inversion and atmospheric filtering were selected to obtain more accurate LOS displacement, and the results were projected to the vertical direction according to the geometric relationship of incident angle for further analysis [30,31].…”
Section: Data Processingmentioning
confidence: 99%
“…Satellite-based remote sensing techniques are valuable for damage mapping applications due to global coverage and high spatial resolutions associated with satellite data [3]. Remote sensing using space technology, specifically Interferometric Synthetic Aperture Radar (InSAR) techniques, have successfully been used for different mapping applications such as post-war urban damage mapping [4], digital elevation model (DEM) generation [5], landslide investigation [6], and earthquake-induced damage mapping [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…satellite imagery) (Witmer, 2015;Casciati et al, 2017) and other technologies (Weir et al, 2019;Argyroudis et al, 2022;Knoth et al, 2018) and use of available maps and geospatial analysis to better design recovery of affected cities (Cariolet et al, 2019;Levin et al, 2018). The deployment of satellite imagery and social media crowdsourcing for assessing infrastructure disruptions has been extensively investigated in the past in the context of natural disasters (Kryvasheyeu et al, 2016;Imran et al, 2013;Chen & Hutchinson, 2007) and environmental impact (Arturo Mendez Garzón & Valánszki, 2020) or location and extent of building damage as a result of conflicts (Boloorani et al, 2021). These studies demonstrated the added value brought by aerial surveys to facilitate mainly identification or severity of damage (Chen & Ji, 2021) and very recently to enable adaptive recovery and prioritisation (Kottmann et al, 2021).…”
Section: Introductionmentioning
confidence: 99%